Academic supervision practice: case studies in kindergartens during the Covid-19 Pandemic - Febriyanti, Kurnia; Rohmadheny, Prima Suci; Rahma Wati, Yuning Eka (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
Academic supervision at TK LKMD Ngambah by the headmaster before the pandemic only completed, the teaching observation step and was carried out directly. With the change in education policy during a pandemic, there is a background in this research. For this reason, the purpose of this study is to explore and describe in-depth information about the implementation of school headmaster academic supervision during the pandemic at TK LKMD Ngambah.The present study employed qualitative research with a case study approach. One headmaster and three teachers participated as the research subjects. Interviews, focus groups, and documentation were utilized to collect the research data. The study used source triangulation and member checks to assess the data validity. In analyzing the data, the Spradley model was completed. The results that the implementation of academic supervision at TK LKMD Ngambah during the pandemic was in accordance with the stages of academic supervision and the implementation was still carried out directly even though learning was online. Furthermore, the learning support documents were not thoroughly examined and the filling-out of the assessment instrument was manipulated.